Protein and Amino Acid Supplementation Levels for Broilers in Pre-Starter Ration - Stringhini, Jose Henrique; Andrade, Michelle Lobo; Xavier, Suzany Aparecida Gomes; Andrade, Maria Auxiliadora; Minafr, Cibele Silva; Cafe, Marcos Barcellos (International Journal of Poultry Science, 2009)
Performance, ether extract, dry matter and protein digestibility and enzymatic activities of broilers fed different Crude Protein (CP) and amino acid levels in pre-starter ration were evaluated. 560 MPK male day-old chicks were raised until 21 days of age in heated brooders and allotted in a complete randomized design with eight treatments and five replicates each: A. 20% CP non-supplemented; B. 20% CP supplemented with Met, Lys and Thr; C. 20% CP supplemented with Met, Lys, Thr and Trp for 22% CP; D. 20% CP supplemented with Met, Lys, Thr and Trp for 24% CP; E. 22% CP non-supplemented; F. 22% CP supplemented with Met, Lys and Thr; G. 22% CP supplemented with Met, Lys, Thr and Trp for 24% CP; H. 22% CP supplemented with Met, Lys, Thr and Trp for 26% CP: All diets attended amino acid requirements of Rostagno et al. (2000) for corn-soybean rations with 2.900 Kcal/kg ME from 1-7 days. From 8-21 days, broilers received the same starter ration with 21.1% CP and 2900 Kcal/kg ME. The weight gain, feed intake and feed-to-gain ratio for total period and digestibility index and retention for Dry Matter (DM), CP (CP) and Ether Extract (EE) and digestibility parameters were measured from 4-7 days. In the 4th, 7th, 10th and 14th days of age, the pancreas of four birds was collected to amylase and tripsin analysis. The means were calculated and the Tukey test (p